2015
DOI: 10.3126/kumj.v12i1.13628
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Clinical and Endoscopic Profile of Acute Upper Gastrointestinal Bleeding

Abstract: Backgroud Acute Upper Gastrointestinal Bleeding is a common medical emergency with a hospital mortality of approximately 10 percent. Higher mortality rate is associated with rebleeding. Rockall scoring system identifies patients at higher risk of rebleed and mortality.Objective To study the clinical and endoscopic profile of acute upper gastrointestinal bleed to know the etiology, clinical presentation, severity of bleeding and outcome.Method This is a prospective, descriptive hospital based study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
3
24
1
Order By: Relevance
“…The mean age in this study in patients presenting with UGIB was 47.87±16.16years, which was comparable to several past studies. 5 11.92% UGIB patients had a normal endoscopy in this study, which was similar to 13.9% of Cotton PB et al 12 Most UGIB patients in this study presented with hematemesis with malena, followed by hematemesis, similar pattern has also been reported by Dewan KR et al 13 More than half (52.94%) of the UGIB cases were attributed to portal hypertension i.e. esophageal or gastric variceal bleed.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The mean age in this study in patients presenting with UGIB was 47.87±16.16years, which was comparable to several past studies. 5 11.92% UGIB patients had a normal endoscopy in this study, which was similar to 13.9% of Cotton PB et al 12 Most UGIB patients in this study presented with hematemesis with malena, followed by hematemesis, similar pattern has also been reported by Dewan KR et al 13 More than half (52.94%) of the UGIB cases were attributed to portal hypertension i.e. esophageal or gastric variceal bleed.…”
Section: Discussionsupporting
confidence: 87%
“…7,8 Erosive Gastroduodenitis, was the third commonest cause of UGIB (12.28%), which was similar to that suggested by recent work by Dewan KR et al, (11%) but significantly higher than 9% as suggested in some older Indian studies. 7,8,13 This may be attributed to changing lifestyle pattern, diet, frequent use of alcohol and over the counter NSAIDS.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Pakistan, Islamabad concluded that variceal bleeding is a common cause of UGIB in Pakistan. 14 Both the studies of Pakistan which is quoted in this study commented upon high prevalence of cirrhosis due to hepatitis leading to varices as a cause of UGIB. In our study variceal bleeding was the most important cause however unlike both these studies from Pakistan, alcoholic cirrhosis was the most common cause of varices, while they reported that hepatitis is the common cause for the cirrhosis.…”
Section: Discussionmentioning
confidence: 77%
“…Similar prevalence studies are done in India as well as from other developing countries. [9][10][11][12][13][14][15][16][17] As studies are from different geographical locations and having different infrastructural facilities, results in relation to causes, clinical profile and outcome may vary. Table no 6 shows analysis of different studies having almost similar objectives of their research.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The prevalence of esophageal varices in LC is around 80%-90% 5,6 and variceal hemorrhage occurs at a rate of 10%-30% yearly. 7 Two studies from Nepal have shown esophageal varices as the cause of upper GI bleeding in 47.5% 8 and 15.6% 9 cases respectively.…”
Section: Introductionmentioning
confidence: 99%